1997
DOI: 10.1073/pnas.94.6.2518
|View full text |Cite
|
Sign up to set email alerts
|

T cell receptor restriction of diabetogenic autoimmune NOD T cells

Abstract: Restricted use of T cell receptor (TCR) gene segments is characteristic of several induced autoimmune disease models. TCR sequences have previously been unavailable for pathogenic T cells which react with a defined autoantigen in a spontaneous autoimmune disease. The majority of T cell clones, derived from islets of NOD mice which spontaneously develop type I diabetes, react with insulin peptide B-(9-23). We have sequenced the ␣ and ␤ chains of TCRs from these B-(9-23)-reactive T cell clones. No TCR ␤ chain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
79
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 25 publications
0
79
1
1
Order By: Relevance
“…Regarding autoreactive CD4 + T cells that may show a more restricted TCR repertoire diversity due to negative selection, previous studies revealed a prevalent TCRβ clonotype usage for CD4 + T cells specific for glutamic acid decarboxyase 65 (GAD65) in NOD mice or for myelin basic protein-specific CD4 + T cells in SJL mice yet the TCRα repertoire of these autoreactive CD4 + T cells was not characterized [23,24]. However, a prevalent role of the TCR Vα chain in the recognition of the insulin B9-23 epitope by autoreactive CD4 + T cells in the NOD mouse has been documented, although, the CDR3α motifs were diverse [25]. The repertoire of encephalogenic CD4 + T cells specific for myelin oligodendrocyte glycoprotein (MOG) is also dominated by few clonotypes expressing restricted TCRα and β rearrangements [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding autoreactive CD4 + T cells that may show a more restricted TCR repertoire diversity due to negative selection, previous studies revealed a prevalent TCRβ clonotype usage for CD4 + T cells specific for glutamic acid decarboxyase 65 (GAD65) in NOD mice or for myelin basic protein-specific CD4 + T cells in SJL mice yet the TCRα repertoire of these autoreactive CD4 + T cells was not characterized [23,24]. However, a prevalent role of the TCR Vα chain in the recognition of the insulin B9-23 epitope by autoreactive CD4 + T cells in the NOD mouse has been documented, although, the CDR3α motifs were diverse [25]. The repertoire of encephalogenic CD4 + T cells specific for myelin oligodendrocyte glycoprotein (MOG) is also dominated by few clonotypes expressing restricted TCRα and β rearrangements [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, a prevalent role of the TCR Vα chain in the recognition of the insulin B9-23 epitope by autoreactive CD4 + T cells in the NOD mouse has been documented, although, the CDR3α motifs were diverse [25]. The repertoire of encephalogenic CD4 + T cells specific for myelin oligodendrocyte glycoprotein (MOG) is also dominated by few clonotypes expressing restricted TCRα and β rearrangements [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike MOGreactive T cell clones, not all of the PLP-reactive clones needed the same nonameric core epitope for their stimulation [35]. In other studies describing T cells reactive against MBP89-101 in SJL/J mice [36,37], against antigens/epitopes in rheumatoid arthritis (such as collagen II [38][39][40]) or against antigens/epitopes in type I diabetes (such as insulin [41,42] or glutamic acid decarboxylase 65 [43,44]), both restricted and highly diverse TCR repertoires have been reported to be associated with reactivity to the disease-relevant antigen/epitope. However, in the studies where diverse TCR expression for recognition of the epitopic region was demonstrated, the nonameric core sequence essential for stimulation of the heterogeneous T cells was not assigned [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…The endogenous MuLV envelope protein may retard the immune aggression to cells rather than accelerating the onset of IDDM. Since the same amino acid sequences suppressing the cellular immunity were located in our MuLV envelope protein [41,42], our endogenous MuLV envelope protein would reduce the cellular immunity against cell [29]. In fact, the long duration of insulitic stage before onset of IDDM and high expression of MuLV envelope gene during this stage suggests the existence of immune suppression.…”
Section: Discussionmentioning
confidence: 97%
“…Another possible role of retroviral envelope protein in the pathogenesis of IDDM is that the endogenous MuLV retroviral protein acts as superantigen. Since it was reported that there is some bias or loss of specific subset of T cell in NOD immune system, a superantigen can be involved in the development of IDDM [41]. Especially, Conrad et al reported that the N-terminal end of human endogenous retroviral envelope protein had the superantigenic activity [36].…”
Section: Discussionmentioning
confidence: 99%